TEACHERS’ READINESS TO IMPLEMENT INQUIRY FOR SCIENCE INSTRUCTION IN ELEMENTARY SCHOOL - Budiastra, A.A. Ketut; Purwoningsih, Tuti (IJRDO- Journal of Educational Research, 2017)
This study aims to know teachers’ readiness in implementing inquiry for science instructions in elementary school. This study implemented dominant less dominant design or mixed method. The data was collected using purposive sampling technique. There were 90 elementary school teachers from three regional offices, namely Pangkalpinang, Serang, and Denpasar as respondents for this study. The instruments used for this study was a questionnaire as the main data collection, in addition to an interview and an observation form. 27 teachers from three regional offices were observed using the form for Teacher Performance Assessment Instrument (TPAI). This instrument consists of two parts, TPAI-1 for assessing the lesson plans and TPAI-2 for assessing the performance of teachers in actuating the instruction. An in-depth interview was conducted for 27 elementary school teachers after the observation. On the one hand, the result shows that only a few teachers can be categorized ready for implementing inquiry for science instruction. This was concluded from the appraisal of teachers’ preparation and their activities during the instruction process. On the other hand, a large number of teachers can be categorized not ready to implement inquiry for science instruction. Lack of knowledge and information regarding the importance of inquiry in science instruction can be mentioned as one of the obstacles in implementing inquiry for science instruction. From this study, it is recommended that inquiry for science instruction needs science equipment. However, the most important thing is an inquiry for science instruction needs teachers to change their mindset that science instructions for elementary school must be taught by inquiry.